Re-Interpreting the Values and Symbols of Javanese Character Education for Children in Yogyakarta - Ichsan, Ahmad Shofiyuddin; Trimansyah, Trimansyah; Khunaivi, Herman; Al Basyari, M. Mahbub; Maulana, Ardian (Fitrah, 2025)
Javanese society, especially in Yogyakarta, has a strong bond with norms of life, traditions, and religion and is still maintained in everyday life to this day. The values ​​shown in their lives have their own symbols with noble meanings in them. This research aims to reveal the values ​​and symbols in character education of children in Yogyakarta as a symbol of Javanese society. The researchers used qualitative research with data collection techniques through observation, in-depth interviews, and documentation. The researchers used data analysis in this research through the Miles and Huberman model with three stages, namely data reduction, data presentation, and conclusion. The research results indicate that the philosophy of life of the Yogyakarta community has been used as a character education value for children with an emphasis on attitudes that need to be maintained by children, attitudes that must be avoided, values ​​and symbols in the seriousness of facing life for children, the relationship between children and their God, and the relationship between children and other creatures. These various attitudes continue to be developed by children as a noble culture that holds many noble values ​​and symbols, so that in themselves children are created strong characters.